PRODUCTION PROCESS OPTIMIZATION TO MINIMIZE GLUE WASTE AT PT TRIMITRA SEJATI JAYA SIDOARJO - Alfiandy, Muhammad Yafie; Handayani, Wiwik (Yayasan Education and Social Center, 2024)
Many companies compete to make high quality products. The companys goals are in line with the implementation of lean manufacturing. PT Trimitra Sejati Jaya is a company engaged in the hotmelt adhesive and white PVAC glue industry. In facing competition with competitors, PT Trimitra Sejati Jaya is expected to have an efficient and effective production process. Therefore, the aim of this research is to find non-value-added activities and seven wastes on the production floor in order to increase the efficiency of the company's production process through the process activity mapping method. The results of process activity mapping on production activities show that the process cycle efficiency of raw materials and documents has the lowest efficiency level of 2.33%, and the production process has the highest efficiency level of 99.69%, while the waste that dominates is waiting, motion, and transportation with a total cycle process of 68.34%. This research produces suggestions for improvements, namely the use of virtual collaborative workspaces, running the 5S program, and using a quality control system